2013
DOI: 10.1016/j.ejvs.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Reverse Thermosensitive Polymer to Achieve Temporary Atraumatic Vessel Occlusion in Infra-popliteal Bypasses

Abstract: This thermosensitive polymer is a potentially safe and useful atraumatic device to achieve a blood-less distal anastomotic field in infra-popliteal bypasses. The technique avoids other potentially traumatic methods of vessel control, which may be particularly important in patients with calcified distal vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…( C ) Optical image of a monodisperse population of 10 μm diameter microspheres. Reproduced with permission from [23]. Copyright (2005) American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…( C ) Optical image of a monodisperse population of 10 μm diameter microspheres. Reproduced with permission from [23]. Copyright (2005) American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…This has shown early promising results in peripheral bypass surgery when used as a safe and atraumatic device to achieve a bloodless distal anastomotic field, 47 including its use in infrapopliteal bypass surgery. 48 A recent systematic review of LeGoo use in infrainguinal bypass surgery demonstrated a primary technical success rate of 90% and limb salvage rate of 78%, although the evidence reviewed was very heterogeneous. 49…”
Section: Managing the Fragile Anastomosis: Clampless Surgerymentioning
confidence: 99%